Alginate Oligosaccharide Prevents against D-galactose-mediated Cataract in C57BL/6J Mice via Regulating Oxidative Stress and Antioxidant System. (3rd June 2021) - Feng, Wenjing; Yang, Xuejiao; Feng, Meiping; Pan, Hui; Liu, Jianya; Hu, Yi; Wang, Shan; Zhang, Dongfeng; Ma, Fenghua; Mao, Yongjun
ABSTRACT: Purpose: Alginate oligosaccharides (AOS), obtained from depolymerizing alginate, has multiple pharmacological benefits. Cataract is a common disease caused by turbidity of the lens protein due to lens metabolism disorders. This study aimed to test the effects and the underlying mechanisms of AOS on D-galactose (D-gal)-mediated cataract. Materials and Methods: A total of 45 8-week-old C57BL/6 J male mice were randomly divided into 5 groups. After eight weeks' intervention, the score of cataract was calculated depending on the turbidity of the lens. Hematoxylin and eosin (HE) and transmission electron microscope (TEM) images were observed. Superoxide dismutase (SOD) activity and malondialdehyde (MDA) level were measured by corresponding detection kits, respectively. SOD1, SOD2, catalase (CAT) and p53 protein expressions were examined by Western blot. Nuclear factor erythroid-2 related factor (Nrf2) and heme oxygenase-1 (HO-1) mRNA expressions were examined by Quantitative Real Time-PCR (RT-qPCR). Results: The score of the turbidity of the lens showed that AOS significantly delayed the cataractogenesis. HE staining and TEM imaging showed that AOS decreased the damage and senescence of lenses in D-gal-induced C57BL/6 J mice. We further detected aging marker p53 expression in crystalline lenses, and our result showed that AOS significantly inhibited p53 protein expression in D-gal-induced mice. In addition, SOD activity and MDA level detection results showed that AOS significantly increased the activity of SOD, and decreased the level of MDA in crystalline lenses homogenates of D-gal-induced aging mice. Western blot results showed that AOS attenuated the damage of D-gal in the protein expressions of antioxidative enzymes SOD1, SOD2 and CAT. RT-qPCR results showed that AOS suppressed the down-regulation of Nrf2 and HO-1 mRNA expressions induced by D-gal. Conclusions: AOS prevents against D-gal-mediated cataract in C57BL/6 J mice via inhibiting oxidative stress and up-regulating antioxidant system. Consequently, our results suggest that AOS may be an effective therapeutic strategy against cataract.